Respuesta :

Answer:

Step-by-step explanation:

[tex][(\sqrt[4]{x^{\dfrac{3}{4}}})^{\dfrac{-4}{3}} ]^{4}[/tex]

[tex]= [(x^{\frac{3}{4}*\frac{1}{4}})^{\frac{-4}{3}}]^{4}\\\\\\= [(x^{\frac{3}{16} ) ^{\frac{-4}{3}}}]^{4}\\\\=[ x^{\frac{3}{16}*\frac{-4}{3}}]^{4}\\\\=[x^{\frac{-1}{4}}]^{4}\\\\=x^{\frac{-1}{4}*4}\\\\=x^{-1}\\\\=\dfrac{1}{x}[/tex]

Hint:

[tex](a^{m})^{n}=a^{m*n}[/tex]

Answer:

[tex]1/x[/tex]

Step-by-step explanation:

To simplify, work from the inside out.

We start with

[tex]\sqrt[4]{x^{3/4}}[/tex]

on the inside. And we can change the fourth root into a fractional exponent -- 1/4:

[tex](x^{\frac{3}{4})^{1/4}[/tex]

A power of a power means multiply the exponents, giving

[tex]x^{\frac{3}{4} * \frac{1}{4}} = x^{3/16}[/tex]

So now we have

[tex][(x^{3/16})^{-4/3}]^4[/tex]

From here, apply the "power of a power rule" again, working from the inside out.

[tex](x^{-12/48})^4[/tex]

[tex]x^{-48/48}[/tex]

[tex]x^{-1}[/tex]

or

[tex]1/x[/tex]

ACCESS MORE